Autophagy suppresses TRP53/p53 and oxidative stress to enable mammalian survival. Issue 7 (2nd July 2020) - Yang, Yang; White, Eileen
ABSTRACT: Macroautophagy (hereafter autophagy) plays an important role in maintaining cellular homeostasis under stress conditions. We previously demonstrated that conditional autophagy deficiency in adult mice causes selective tissue damage, is lethal upon fasting, and shortens lifespan to less than three months primarily due to neurodegeneration, but not all the mechanisms are known. We conditionally deleted Trp53/p53 and/or the essential autophagy gene Atg7 throughout adult mice to test whether TRP53 is responsible for any of these phenotypes. atg7 Δ/Δ trp53 Δ/Δ mice have extended lifespan due to delayed tissue damage and neurodegeneration, and are resistant to death upon fasting compared to atg7 Δ/Δ mice. Atg7 also suppresses apoptosis induced by the TRP53 activator Nutlin-3 in liver and brain. We then deleted Atg7 in the presence or absence of the master regulator of antioxidant defense NFE2L2/NRF2 (nuclear factor, erythroid derived 2, like 2) to test if increased oxidative stress causes TRP53 activation in atg7 Δ/Δ mice. nfe2l2 −/- atg7 Δ/Δ mice die rapidly due to intestinal damage, which is not rescued by trp53 co-deletion. Therefore, these data demonstrate the tissue specificities and functional dependencies between autophagy, TRP53 and NFE2L2 stress response mechanisms.